Dental professional training and practice: tensions around the Hegemonic Dental Medical Model - Cortés-Quiroz, María Del Carmen; Jarillo-Soto, Edgar Carlos (Revista Facultad de Odontología Universidad de Antioquia, 2025)
This essay raises a reflection on the education, training and professional dental practice of oral health personnel, elements that articulated give rise to the construction of a Hegemonic Dental Medical Care Model, characterized by the production of a body of knowledge that supports its object of study in dimensions that validate and promote approaches for its understanding, and with them a positioning regarding the individual and collective health-disease-care-oral care process. From which oral health professionals establish technical interventions to face oral conditions, where alternative practices that emerged in the culture and present in the social environment of the subjects to maintain their oral health are frequently unknown or displaced. The final reflections point towards the role of universities, spaces where professional dental practice is scientifically validated and promoted through an established object of study, from which a hegemonic model of dental care is oriented, built, and strengthened, despite the strong, questioning that has occurred in recent years even by professionals in the field themselves exposing the tensions around the training and practice of the profession.